Methods for Mesh Implantation Efficacy Assessment in Rectocele - A. S. Lukianov; A. Yu. Titov; O. M. Biryukov; A. A. Mudrov; I. V. Kostarev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A methodological review on mesh implantation efficacy assessment in surgery for rectocele.Key points. Specialised quiz surveys are among the most appropriate methods to assess surgical intervention efficacy. The questionnaires that enable pre- and postsurgery rectocele grading include PFDI-20 (Pelvic Floor Distress Inventory), the colonic evacuation disorder scale and Cleveland Constipation Scoring System. These surveys determine the surgical intervention efficacy dynamically in conjunction with instrumental surgery assessment techniques.Conclusion. Clinical practice at the Ryzhikh National Medical Research Centre for Coloproctology combines the originally developed colonic evacuation disorder scale (2003) and PFDI-20. The combined scales allow for a comprehensive symptom assessment in patients with rectocele and other descending perineum syndrome manifestations prior to surgery, as well as symptom dynamics evaluation postoperatively, which, in link with defecography, enables a complete appraisal of the surgical effect.